Patients with Active Luminal Crohn's Disease Have Evidence of Significant Functional and Clinical Pulmonary Involvement. Issue 8 (August 2015) - Peerani, Farhad; Choi, May; Weinkauf, Justin; Fedorak, Richard N.; Halloran, Brendan
Abstract : Background: Pulmonary involvement is a recognized extraintestinal complication of inflammatory bowel disease and is associated with airway inflammation. Changes in pulmonary function were previously described as being subclinical. The purpose of this study was to compare pulmonary findings in a large case series of patients with active and quiescent Crohn's disease (CD). Methods: CD patients, prospectively enrolled between May 2011 and May 2012, completed a demographic questionnaire and Harvey–Bradshaw Index to define disease activity. Each patient also completed blood work, a chest x-ray, pulmonary function testing, respiratory symptom and dyspnea scoring, and a 6-minute walk test. Results are reported as mean ± SE or descriptively as a percent and were analyzed using t tests and chi-square or Fisher's exact tests, respectively. Multivariable linear regression models were built for continuous outcomes and logistic regression models for categorical outcomes. Results: Ninety-five patients (54 remission, 41 active disease), 58.9% males, with a mean age of 41 ± 1 years were enrolled. Patients with active disease compared with those in remission had lower absolute ratios of forced expiratory volume in 1 second to forced vital capacity (FEV1/FVC) (0.74 ± 0.01 versus 0.77 ± 0.01, P = 0.023), higher degrees of peripheral airway obstruction (34.1% versus 16.7%, P = 0.049), more frequent respiratory symptoms (29.3% versus 9.3%, P = 0.012) and higher Medical Research Council (MRC) dyspnea scales (MRC 2 or 3, 58.5% versus 22.2%, P = 0.001), respectively. Conclusions: CD patients with active disease display clinical pulmonary dysfunction compared with those in remission. Abstract : Article first published online 18 June 2015.